Pengaruh Laju Alir Umpan Terhadap pH, Alkalinitas Dan Asam Volatil Pada Pengolahan Limbah Cair Kelapa Sawit Menggunakan Bioreaktor Hibrid Anaerob Dua Tahap - Salis, Gita Aziza; Muria, Sri Rezeki; Ahmad, Adrianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Ratio of total volatile acid and alkalinity can represent the stability of bioreactor. Goal of this experiment is to determine the influence of feed flow rate to change of pH, alkalinityand volatile acid in two stage of anaerobic hybrid bioreactor, it also to knows the stability rate of bioreactor that used. Bioreactor that used in this experiment is a bioreactor thathave two pattern of microorganism growth there are suspended and cling phase with rock and palm oil shells as the immobilize media of microorganism cell. Active volume of bioreactor that used in this experiment is 10 liter with variating feed flow rate 1,4; 2; and 3,3 L/day for 2nd stage bioreactor with operation condition pH 6,8 – 7,2 in room temperature. Parameter that analyzed from this experiment is the ratio of volatile acid withalkalinity from bioreactor effluent. In 1st stage of bioreactor, feed flow rate that used is 5 L/day and the result found was average of pH in 6,7; average of alkalinity concentration is2220,8 mg/L and average of volatile acid concentration is 413,52 mg/L so that ratio of TAV/Alkalinity was 0,812. Results of this experiment shows that the highest stability of 2nd anaerobic hybrid bioreactor is 0,033 in smallest feed flow rate 1,4 L/day.Keywords : alkalinity; Hybrid anaerobic bioreactor; stability; Volatile acids